Population Ageing And Income Inequality In China - Yan, Xiao (2024)
Income inequality has become a pressing social issue globally, with China's dramatic increase in inequality since the 1990s drawing significant scholarly interest. The country's inequality levels exceeded international warnings in the late 1990s. Concurrently, China has experienced an unprecedentedly rapid ageing process, projecting it to become the world's largest super-aged nation soon. Demographic shifts impact income disparities across age groups, necessitating an exploration of income inequality among these groups and the age effect on this inequality in China. This thesis has three primary objectives: First, it aims to assess the age effects on income inequality in China using the Theil decomposition method and micro dataset China Family Panel Studies (CFPS). Second, it examines the impact of population ageing on income inequality through mixed Ordinary Least Squares (OLS), fixed effect, and random effect models. Third, it distinguishes between urban and rural populations and compares the age effect of income inequality in the rural and urban areas. Regression analyses were employed to assess the influence of different age groups, educational attainment, and financial sector development on income inequality. The key findings are Income inequality is not uniform across age groups, with the 55-59 age group experiencing the most significant disparities. Population ageing exacerbates income inequality throughout China from 2010 to 2018, with changes in macro-environmental factors and household size also impacting inequality. Moreover, the impact of population ageing is more pronounced in urban areas, while education has a more significant effect on income convergence in rural areas. The study enriches scholarly debate and offers valuable policy implications.